Association of millennial parenting styles, dietary and the incidence of stunting - Silpia, Nana; Palimbo, Adriana; Lestari, Yayuk Puji; Salmarini, Desilestia Dwi (Ananda - Health & Education Foundation, 2025)
Background: Stunng, a chronic nutrional issue among toddlers, connues to be a global and naonal public health concern. It reflects the cumulave effects of inadequate nutrion and poor parenng pracces. Millennial parenng styles and dietary habits play a pivotal role in influencing stunng outcomes, parcularly in regions like Banjarmasin, Indonesia. Objective: This study aims to analyze the correlaon between millennial parenng styles, dietary paerns, and stunng incidence among toddlers in the Pekauman Health Center area. Methods: A cross-seconal study was conducted in May 2024 involving 127 toddlers aged 2–5 years and their parents. Data were collected using height measurements and validated quesonnaires on parenng styles and dietary pracces. Chi-square tests were employed to analyze relaonships, with a significance level of α = 0.05. Results: The study revealed that 64.6% of toddlers were stunted. Among parents, 61.4% exhibited a